When human rights and migration policies are not consistent: an overview of European policies with emphasis on italian policies - Lara Salinas, Ana María (Sociedad y Economía, 2010)
Migration policies are increasingly restrictive. The European Union Return Directive shows this. Italy plays a key role in this dynamic. Analyze the causes and factors which are motivating policies in this direction as well as political, social and economic changes and their impacts are the objectives of this article. The shortcomings in diplomacy with the countries of migration origin will be the final challenge which concludes. .